Answers

2016-05-22T10:45:50+08:00

2-2√-3/2, 2+2√-3/2
I used quadratic equation because you equation is not factorable.
0
2016-05-27T00:05:55+08:00
   x² -2 x + 4   =   0
   x² -2 x    = - 4
  x² -2 x + (-2/2)²   =  - 4 + 1  /  to make the left side a perfect square I add 1 to                                                       both sides of the equation
  thus (x-1)²   =    - 3
           x-1   =   + or -  √ -3        / take the √    of both sides
           x =  1 + √ -3     or  1 - √-3
               x   =   1 + i√3   1 - i√3
0